A descriptive study of the relationship between preoperative body temperature and intraoperative core temperature change in adults under general anaesthesia - Steyn, Francois (Department of Anaesthesia and Perioperative Medicine, 2023)
Background: Despite numerous guidelines on perioperative temperature management, perioperative hypothermia remains common. Prewarming to prevent redistribution hypothermia is supported by evidence, but not widely practiced. We investigate the measurement of preoperative mean body temperature as a potential tool for individualising the practise of prewarming. Methods: We hypothesised that patients who experience intraoperative hypothermia have a lower preoperative mean body temperature. A longitudinal study was conducted in adult patients presenting for ophthalmological surgery under general anaesthesia, to describe the relationship between the incidence of hypothermia within the first hour of anaesthesia and preoperative mean body temperature. Results: Sixty-five patients were enrolled. Twelve participants (18%) presented to the operating theatre hypothermic (core temperature <36.0°C). A further twenty-eight (43%) became hypothermic during the procedure. All hypothermia events occurred within sixty minutes after induction of anaesthesia, and half of the events occurred within nineteen minutes. The difference in preoperative mean body temperature between those with- and without intraoperative hypothermia was only -0.2°C (95% CI -0.4, 0.1). This is neither clinically relevant nor statistically noteworthy. In Cox proportional hazards analysis, BMI and ASA status compounded the observed association between preoperative mean body temperature and the incidence of intraoperative hypothermia. A higher BMI and ASA are associated with a lower incidence of hypothermia. Conclusion: We conclude that intraoperative hypothermia is common and occurs early after induction of anaesthesia. We observed no useful difference in preoperative mean body temperature to help distinguish between patients who become hypothermic and those who do not. Without a useful risk prediction tool, a generic approach to prewarming remains appropriate. Preoperative screening for pre-existing hypothermia should be practiced, even in cases considered as low risk.